Problems Related to the Exercise of Custody Rights in Algeria: Between Legal Texts and Judicial Practice - Benaichouche, Omar; Djillali Bentayeb, Djillali (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2024)
This research addresses the problems related to exercising custody rights in Algerian legislation. As one of the critical legal consequences of marital dissolution, custody is crucial for ensuring the child's welfare. Islamic law approves custody, and statutory laws have followed suit, prompting an investigation into the legal issues arising from its judicial application. This study is structured into two main axes: the first examines issues related to alimony and house rent allowance, and the second addresses the challenges of visiting and transporting the child in custody. Using a descriptive-analytical approach, we analyzed rulings and decisions issued by the Algerian judiciary. The study found that while Algerian family law stipulates provisions for custody, many loopholes revealed through judicial practice make these provisions incompatible with Algerian society's social and economic conditions. Our findings highlight the need for legislative amendments to address these discrepancies.